MENYINGKAP KARAKTER MASYARAKAT MANDAILING MELALUI UMPAMA - Anharuddin Hutasuhut (Balai Bahasa Sumatera Utara, 2019)
This research studies character of Mandailing dealing with Mandailingparables. The research data are Mandailing parables containing the nature,behavior, or moral concept of Mandailing. The theory used in this research is semantic (Pateda, 2001). Based on the results of analysis, it is concluded that there are 11 Mandailing positive characters, they are (1) patriotic, (2) hardworking, (3) courteousness, (4) honest, (5) democratic, (6) social awareness, (7) responsible, (8) fair, (9) knowledge able, (10) modest, and (11) allertness. Furthermore, there are 7 negative characters of Mandailing: (1)hypocrite, (2) tricky, (3) unfair, (4) temperament, (5) lazier, (6) arrogant, and (7) materialist.